Day 2 Tue, October 17, 2017 2017
DOI: 10.2118/187684-ms
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Development of Tight Reserves of the V. Vinogradov Field using Multi-Stage Hydraulic Fracturing

Abstract: The work describes the implemented techniques which help optimize reservoir engineering for tight oil deposits with the usage of multi-stage hydraulic fracturing by up-to-date methods of fracturing values’ evaluation. The work also identifies reasons of high water cut of well production after the multi-stage hydraulic fracturing at the V. Vinogradov field. The work also describes principles of preparing and implementing the optimum design of the multi-stage hydraulic fracturing under the conditions of unconstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Many studies related to multi-stage fracturing in thick tight sandstone reservoirs have been conducted (Karpov et al., 2017; Li et al., 2018; Lu et al., 2015; Olson and Taleghani, 2009). Olson and Taleghani (2009) suggested that hydraulic fractures could propagate across natural fracture planes without deviation and without additional leak-off under certain conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies related to multi-stage fracturing in thick tight sandstone reservoirs have been conducted (Karpov et al., 2017; Li et al., 2018; Lu et al., 2015; Olson and Taleghani, 2009). Olson and Taleghani (2009) suggested that hydraulic fractures could propagate across natural fracture planes without deviation and without additional leak-off under certain conditions.…”
Section: Introductionmentioning
confidence: 99%